2022
DOI: 10.1111/joim.13572
|View full text |Cite
|
Sign up to set email alerts
|

Associations of plasma TMAO and its precursors with stroke risk in the general population: A nested case‐control study

Abstract: Background. Trimethylamine N-oxide (TMAO) is a gut-derived atherogenic metabolite. However, the role of TMAO and its precursors in the development of stroke remains unclear. We aimed to examine the associations between metabolites in TMAO biosynthesis and stroke risk. Methods.A nested case-control study was performed in a community-based cohort (2013-2018, n = 16,113). We included 412 identified stroke cases and 412 controls matched by age and sex. Plasma carnitine, choline, betaine, trimethyl lysine (TML), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Details of the Prospective Follow-up Study on Cardiovascular Morbidity and Mortality in China (PFS-CMMC), including study strategy and enrollment, have been previously described [ 16 , 17 ]. In summary, after excluding individuals with severe cancer, severe disability, and/or severe psychiatric disturbance, a total of 16,457 residents aged 35 to 74 years in Changshu (Jiangsu province, China) were recruited in 2013.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the Prospective Follow-up Study on Cardiovascular Morbidity and Mortality in China (PFS-CMMC), including study strategy and enrollment, have been previously described [ 16 , 17 ]. In summary, after excluding individuals with severe cancer, severe disability, and/or severe psychiatric disturbance, a total of 16,457 residents aged 35 to 74 years in Changshu (Jiangsu province, China) were recruited in 2013.…”
Section: Methodsmentioning
confidence: 99%
“…Research has not conclusively established a clear link between choline intake and the risk of CVD [ 6 ], and persistent adherence to a high-choline diet may lower CVD-related mortality by addressing inflammation and associated risk factors [ 7 ]. Elevated plasma choline levels are also associated with increased susceptibility to major adverse cardiac events [ 8 ], and heightened trimethylamine N-oxide (TMAO), a choline metabolite, has been identified as a potential risk factor for stroke [ 9 ]. In the field of oncology, a meta-analysis of eleven scholarly articles indicated a possible inverse correlation between increased choline intake and overall cancer risk [ 10 ].…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…In this issue of the Journal of Internal Medicine , Liu et al. [1] report that plasma levels of trimethylamine N‐oxide (TMAO)—but not plasma levels of its metabolic precursors choline, carnitine, betaine, and trimethyl lysine—were associated with the risk of stroke. From a community‐based cohort of 16,113 persons recruited from 2013 to 2018, the authors identified 412 cases of first stroke (321 ischemic and 91 non‐ischemic) over a median follow‐up of 5.3 years and compared them with 412 controls matched for age and sex.…”
mentioning
confidence: 99%
“…The role of the intestinal microbiome in the findings of Liu et al. [1] is revealed by their finding that high levels of plasma TMAO, but not of its metabolic precursors, were associated with stroke risk.…”
mentioning
confidence: 99%
See 1 more Smart Citation